Religious pilgrimage routes and trails : sustainable development and management - Olsen, Daniel H., 1973-; Trono, Anna (CABI religious tourism and pilgrimage series., 2018)
Through a combination of theoretical and case-study chapters, this volume focuses on religious routes and trails in terms of their spiritual, cultural and economic meanings, and considers the opportunities and challenges arising from their recent increase in popularity. The book is divided into three sections. Part I (chapters 1-5) deals with conceptual and practical issues related to religious pilgrimage routes and trails in terms of sustainable local development, regional economic development, heritage identity and management, and environment and sustainability. Part II (chapters 6-19) focuses on case studies related to religious pilgrimage routes and trails from different regions around the world. In Part III, chapter 20 concludes the volume by focusing on the ways in which pilgrimage and religious tourism along religious pilgrimage routes and trails can continue to add to expressions of regional identity and opportunities for regional development. The book includes a list of discussion points and a subject index